Too Hard to Get - Oguntoye, Jide (Rasmed Publications Ltd, 2004)
Kola Abere got married to Felicia and she was made to believe that Peju Ojo is Kola's relation. Hitherto, Peju was regarded as a Sister in law by Felicia.Felicia got transferred out of her base to another town and this gave Kola and Peju the chance to continue with their illicit affairs.
Keywords: Betrayal; Drama; Nigeria